1993
DOI: 10.1161/01.atv.13.6.886
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation at the beta-fibrinogen locus in relation to plasma fibrinogen concentrations and risk of myocardial infarction. The ECTIM Study.

Abstract: Increased plasma fibrinogen concentration is a major cardiovascular risk factor. Conflicting results on genetic variations in plasma fibrinogen levels have been reported. Furthermore, whether flbrinogen genotype is associated with the risk of ischemic heart disease has not been studied so far. An HaelU restriction fragment length polymorphism of the ^-fibrinogen gene was used in a case-control study to investigate the genetic variation at this locus in relation to plasma fibrinogen concentrations and the risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
68
8
4

Year Published

1997
1997
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(97 citation statements)
references
References 22 publications
(19 reference statements)
17
68
8
4
Order By: Relevance
“…13,21,23,[37][38][39][40][41][42] It appears from these studies that the overall impact of the Ϫ455G/A polymorphism on the plasma fibrinogen concentration is rather small. For instance, investigators from the Copenhagen City Heart Study 13 reported that the Ϫ455G/A polymorphism explained only 1% of the variation in plasma fibrinogen level.…”
Section: Discussionmentioning
confidence: 85%
“…13,21,23,[37][38][39][40][41][42] It appears from these studies that the overall impact of the Ϫ455G/A polymorphism on the plasma fibrinogen concentration is rather small. For instance, investigators from the Copenhagen City Heart Study 13 reported that the Ϫ455G/A polymorphism explained only 1% of the variation in plasma fibrinogen level.…”
Section: Discussionmentioning
confidence: 85%
“…Because several studies have suggested variable effects of ␤-fibrinogen genotype on plasma fibrinogen levels in cases with IHD and in controls within the same study (9)(10)(11)19), the effect of ␤-fibrinogen genotype on plasma fibrinogen was examined in women and men with and without IHD. The A-allele was associated with significant increases in plasma fibrinogen in women and men both with and without IHD (Fig.…”
Section: ␤-Fibrinogen Genotype and Plasma Fibrinogen In Individuals Wmentioning
confidence: 99%
“…Of the polymorphisms studied to date, the ( G Ϫ 455 → A ) substitution in the 5 Ј flanking region of the ␤ -fibrinogen gene is associated with the most consistent differences in plasma fibrinogen levels in both casecontrol studies, and in selected groups of healthy individuals (9)(10)(11)(12). Whether fibrinogen genotype actually affects plasma fibrinogen levels and risk of IHD in the general population has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma fibrinogen levels were determined using methods described by Scarabin et al 27 and are reported in mg/dl.…”
Section: Measurement Of Plasma Fibrinogen Levelsmentioning
confidence: 99%